Analisis Proses Pembuatan Biola berbahan Potensi Lokal Bambu sebagai Sumber Belajar IPA SMP/MTs - Dewi, Arum Mustika; Noor, Faiq Makhdum (Universitas Garut, 2025)
This study aims to analyze the relationship between the process of making bamboo violins and science learning materials at the junior high school/Islamic junior high school level, and to find out the teacher's response to the suitability of learning resources based on local potential in the process of making bamboo violins. The abundant local potential of bamboo in Japan Village, Kudus, is utilized by a craftsman named Mr. Ngatmin as the main raw material in making bamboo violins. This study uses a descriptive qualitative approach with data collection techniques in the form of observation, interviews, documentation, and science teacher questionnaires. The results show that all stages of making a bamboo violin from material selection, cutting, drying, processing the violin body, assembly, polishing, to finishing can be linked to science materials, such as plant classification, force and effort, heat, adhesion and cohesion, pressure, physical and chemical changes, and the concept of sound and vibration. The responses of science teachers indicate that the teaching materials based on local potential are considered suitable and interesting to use in learning because they are contextual, relevant to everyday life, and can improve students' understanding and creativity. Keywords: violin, bamboo, local potential, science